Correlation between physical activity and burnout amongst allied healthcare professionals in eThekwini, South Africa - Jeanne Martin Grace; Léchay Moodley (SAGE Open Medicine)
Background: Allied healthcare professionals face the intricate challenge of preventing burnout, which is marked by emotional exhaustion, depersonalisation and diminished personal accomplishment. Physical activity is proposed as a mitigating strategy that promises to reduce and effectively address burnout among allied healthcare professional. Aim: The study aimed to determine the correlation between personal accomplishment and burnout among allied healthcare professionals. Methods: A quantitative, non-experimental, cross-sectional, correlational design following the TREND statement amongst 82 allied healthcare professionals was conducted using the Maslach Burnout Inventory and the Global Physical Activity Questionnaire. Burnout was assessed using its three diagnostic characteristics: emotional exhaustion, depersonalisation and personal accomplishment. Results: Participants (45.1%) experienced a low degree of emotional exhaustion, but overall, for the entire group emotional exhaustion was moderate ( M  = 20.51; standard deviation = 10.5), similar to depersonalisation ( M  = 6.46; standard deviation ±4.90), with 46.3% of the participants experiencing a low degree of depersonalisation. In the personal accomplishment category, 22% experienced a low degree of personal accomplishment; overall, for the entire group, personal accomplishment was low ( M  = 33.35; standard deviation = 7.58). Most participants (65.9%) engaged in moderate-intensity physical activities. The number of days performing moderate-intensity physical activity at work significantly increases the odds of allied healthcare professional experiencing low levels of emotional exhaustion, depersonalisation and personal accomplishment by 1.92, 2.33 and 2.09, respectively ( p  < 0.05). Conclusions: Engaging in moderate-intensity physical activities increases the likelihood of allied healthcare professionals experiencing low emotional exhaustion, depersonalisation and personal accomplishment degrees. It underscores the importance of implementing physical activity programmes to improve healthcare and alleviate the effect of burnout in allied healthcare professional.